Peningkatan Keterampilan Menulis Teks Eksplanasi Melalui Media Audio Visual pada Siswa Kelas XI SMK Negeri 1 Palembang - Siti Rukiyah; Sri Wahyuni Indarawati; Ida Laila (Universitas Batanghari Jambi, 2023)
Based on the results of improving learning carried out through Classroom Action Research (CAR), it can be concluded that the use of audio-visual media can improve the skills of writing explanatory texts at SMK Negeri 1 Palembang class XI AKL 1 in Indonesian subjects with the sub-subjects of explanatory texts as follows. The results obtained by students during the learning improvement activities in the first cycle of students who have obtained a score of 70 reach 17 students with an average score of 59, the student activity score is 44% and the learning completeness is 50%. Then the second cycle of students who get a score of 70 reaches 31 students with an average score of 83, the student activity rate is 91% and the learning completeness has reached 91%. Thus the desired target has been achieved and student learning outcomes have reached the KKM